Los Derechos Humanos como criterio de acceso a la Unión Europea - González del Pino, Silvia (2023)
The European Union (EU) has progressively taken over the concept of human rights, not only because of its wish of bringing different European peoples together, but also because these rights have become, for the EU, a mechanism of legitimating its own existence. Consequently, the EU has established respect for these rights as an accession condition fo r the new Member States of the 2004 and 2007 enlargements, as well as for the candidates that would join in the future. However, there are some doubts about how this conditionality works, since the concept of human rights used by the EU is not clear, and it does not seem coherent with other EU policies in which these rights are also involved. It could be said that the EU has looked, more than for a legal criterion, for a mechanism of political conditionality adaptable to the current necessities and situations, which enables the EU to use different arguments and differe nt levels of requirements according to the specific political context.